Institucionalização científica da economia política da informação: contributos sociais e cognitivos na produção científica do campo da Ciência da Informação no Brasil - Câmara, Rafael Silva da (2020)
It presents the social and cognitive contributions in the process of scientific institutionalization of the Political Economy of Information in the scientific production of the field of Information Science in Brazil. Although a topic foreseen in the area, the Political Economy of Information appears to be little explored in research in Information Science. It theoretically bases the study with the concepts of Domain Analysis, by Hjorland Birger; Scientific Field, by Pierre Bourdieu and Scientific Institutionalization, by Richard Whitley. It adopts field research and bibliometric analysis in the investigation. In the descriptive and documentary trajectory, it recognizes and raises academic backgrounds of authors who published works in the Working Groups with spaces for the production of knowledge in Information Science in the Brazilian section of the Latin Union of Political Economy of Information, Communication and Culture (Ulepicc). It analyzes the scientific production in political economy recovered in the Reference Database of Articles of Periodicals in Information Science (Brapci) and in the Repertoire of Brazilian Periodical Production of Information Science (RPPBCI). It highlights the sources of information and raises the most frequent keywords. It highlights the most productive authors, the main information paradigms in their work and the main theoretical references through the authors they refer to. It analyzes the predominant areas of the research groups in which the most productive authors develop activities. In the field trajectory, he dialogues with researchers recognized for their scientific and academic relevance in the line of study and research in the political economy of information, communication and culture, by conducting interviews in the city of Maceió, in order to raise other pertinent information and that enrich the analysis. He realizes that the Brazilian chapter of Ulepicc and its associates directly interfere in the larger domain of Political Economy of Information, Communication and Culture. It finds that the scientific journal Liinc em Revista is the main channel of scientific communication in the area of Information Science that publishes research papers and results in political economy of information. The results show that Information Science continues in its social institutionalization with regard to the recognition of scientific production and research groups. However, cognitive institutionalization remains a theoretical and epistemological challenge in the area, where issues of language consensus, keywords, research objects and theoretical references present a wide variety in scientific production, in addition to small differences in the reports of the interviewed researchers. He realizes that in the context of interdisciplinarity, the Communication area is the most active and influential in the infocommunication studies of a larger field in Political Economy of Information, Communication and Culture. However, scientific events and journals with an emphasis on this theme have increasingly opened spaces for collaborations in Information Science, which is relevant in the area for strengthening studies of the political economy of information, towards the recognition of researchers, sources and objects of study. Thus, it considers that the socio-cognitive process of scientific institutionalization of the subfield of political information economy in Brazilian Information Science is at a incipient stage.